An overview of effect of process parameters on hydrothermal carbonization of biomass - Nizamuddin, S.; Baloch, H.; Griffin, G.; Mujawar, Mubarak; Bhutto, A.; Abro, R.; Mazari, S.; Ali, B. (Elsevier Science Ltd, 2017)
© 2017 Elsevier LtdThe preceding decades witnessed hydrothermal processes being actively utilized all over the world, specifically in the developed zones. Their optimum usage is primarily sought for in terms of conversion of biomass into valuable solid, liquid and gaseous fuels. Indeed, Hydrothermal carbonization (HTC) is an effective and environment friendly technique; it possesses extensive potential towards producing high-energy density solid fuels. However, the production and quality of solid fuels from HTC depends upon several parameters; temperature, feed type, residence time, pressure and catalyst being the eminent ones. This study investigates the influence of operating parameters on solid fuel production during HTC. The biomass quality has also been analyzed in HTC by extending existing literature work through experiments that have been performed. Data including chemical composition, heating value, proximate analysis and ultimate analysis for different types of biomass was consequently collected and analyzed. It was found that reaction temperature, residence time and type of feed material are the primary factors that influence the HTC process. At higher temperatures, lower solid product is obtained; the carbon content increases, whilst the hydrogen and oxygen content decrease. Further, it has been found that higher lignin content in biomass leads to an increased solid fuel production.